2003
DOI: 10.1109/mwc.2003.1265848
|View full text |Cite
|
Sign up to set email alerts
|

Channel models for ultrawideband personal area networks

Abstract: This article describes the modeling of ultra-wideband wireless propagation channels, especailly for the simulation of personal area networks. The IEEE 802.15.3a standards task group has established a standard channel model to be used for the evaluation of PAN physical layer proposals. We discuss the standard model, the measurements that form its basis, and the possibilities for future improvements. The article points out the important differences between UWB channels and narrowband wireless channels, especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
521
0
8

Year Published

2005
2005
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 735 publications
(532 citation statements)
references
References 10 publications
3
521
0
8
Order By: Relevance
“…UWB benefits from relative immunity to multipath fading and is capable of resolving multipath components with differential delays of 133ps [10] which implies that the existing multipath within this application can be resolved.…”
Section: Multipath Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…UWB benefits from relative immunity to multipath fading and is capable of resolving multipath components with differential delays of 133ps [10] which implies that the existing multipath within this application can be resolved.…”
Section: Multipath Characteristicsmentioning
confidence: 99%
“…Ultra WideBand (UWB) technology has gained huge interest globally due to its potential to deliver high data rate and spatial capacity, with multipath immunity [1,2] and low power, low cost design. The deployment of this wireless technology in vehicles will provide mobility and connectivity to a host of passenger devices while reducing significantly the costs associated with wiring.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significant differences between UWB and narrowband behaviors, existing work has shown that a tapped-delay-line model is appropriate to describe the UWB channels [10], [11]. The channel response can be written as…”
Section: Symbol Detectionmentioning
confidence: 99%
“…Practical values of L depend on the root-mean-squared delay spread of the channel, multipath resolution, and the range of attenuation from the statistically strongest path to the weakest path. Early experimental measurement indicated that the average number of resolvable path is about L = 40 with a 10 dB range (see, e.g., [11]). A RAKE receiver is commonly used to collect these paths coherently to increase the signal strength.…”
Section: Symbol Detectionmentioning
confidence: 99%
“…1 The objective of this paper is to study the suitability and to analyze the (potential) performance of Multiband OFDM for UWB transmission. Thereby, our investigations rely on the new UWB channel model developed under IEEE 802.15 [7]. We analyze this channel model in the frequency domain and 1 Throughout this paper, the term "Multiband OFDM" refers to the particular standard proposal [4], whereas "BICM-OFDM" referes to the general concept of combining BICM and OFDM. extract the relevant statistical parameters that mainly determine the performance of OFDM based transmission.…”
Section: Introductionmentioning
confidence: 99%